NAVIGATING LINGUISTIC SEAS: CODE-MIXING PATTERNS AT INDONESIAN COAST GUARD (BAKAMLA RI) - Nusi, Ahmad; R, Syahrul; Mukhaiyar, Mukhaiyar; Febri Ana Sari, Hindri (Universitas PGRI Sumatera Barat, 2023)
This study examines code-mixing form, function, and patterns within the context of linguistic phenomena at Indonesia Coast Guard (BAKAMLA RI) in East Indonesia, Ambon. To conduct the research, mixed-methode approach was adopted and the data source was a collection of recordings of the students’ utterances in the classroom and workplace. The study found that there were three forms of code mixing used by the students which included words, phrases, and clauses. The data analysis revealed that there were 39 instances of code mixing in the recordings. These 39 instances comprised of 20 data words code mixing, 14 data phrase code mixing, 11 data lexical need code mixing, and 9 data as a function of comment. In addition. code-mixing patterns within the context of linguistic phenomena, specifically focusing on three predominant models: Model of Verb (MoV), Model of Noun (MoN), and Model of Adjective (MoA). The research reveals a total of 158 instances of code-mixing across these models. The results indicated that Model of Verb (MoV) exhibited the highest frequency, constituting 62.03% of the total code-mixing observed. In contrast, Model of Noun (MoN) represented 27.22% of the code-mixing instances, while Model of Adjective (MoA) accounted for 10.75% of the overall code-mixing phenomena. This study sheds light on the use of code mixing in the context of English language teaching and provides new insights into the reasons behind its occurrence in the workplace.